A High-Temperature Molecular Ferroelectric Zn/Dy Complex Exhibiting Single-Ion-Magnet Behavior and Lanthanide Luminescence - Long, Jerome
Multifunctional molecular ferroelectrics are exciting materials synthesized using molecular chemistry concepts, which may combine a spontaneous electrical polarization, switched upon applying an electric...